Remembering capitalism: A. Philip Randolph, Eugene V. Debs, and the town of Pullman - O'Mara, James, author; Dunn, Thomas R., advisor; Dickinson, Greg, committee member; Cauvin, Thomas, committee member (Colorado State University. Libraries, 2019)
Through an analysis of the Pullman National Monument, and President Obama's speech commemorating the town, this thesis demonstrates how the memory of the labor movement within Pullman is framed through a progressive narrative of U.S. history. Throughout the analysis of these artifacts, this thesis examines the material, visual, and textual contours of the public memory surrounding the Pullman town. Building from theories of public address, public memory, public forgetting, and space and place scholarship, my examination of the Pullman National Monument demonstrates the persistence of appeals to liberalism, which actively forgets any alternative to capitalism. This active forgetting serves to stifle the imagination of individuals to develop a working-class politics. Furthermore, in my analysis of President Obama's speech, I offer a theory of the forgetful form to understand how speakers create a desire within the audience to forget problematic elements of the past. Finally, this thesis closes with a discussion of how examining the textuality of a speech, as well as the materiality of a monument together, aid in understanding the public memory of an event.
Keywords: public memory; labor history; rhetoric